A gamified peer assessment model for on-line learning environments in a competitive context. (November 2016) - Tenório, Thyago; Bittencourt, Ig Ibert; Isotani, Seiji; Pedro, Alan; Ospina, Patrícia
Abstract: Peer Assessment (PA) offers a powerful solution that helps teachers in online learning environments to correct essays by distributing the workload among students. Nevertheless, the quality of the results in PA depends on good evaluations of reviewers. Thus, the main drawback for scaling up the use of PA is the presence of inadequate behaviours, such as being too harsh or too soft in the assessment, or even not offering a helpful feedback. This usually occurs due to the lack of motivation and engagement of students in the PA process. To deal with this problem, this paper proposes a gamified peer assessment model, where gamification elements are used to engage students in PA activities. Two experiments using the proposed model within an intelligent tutoring system called MeuTutor shows satisfactory outcomes. We verified that the average grade given by students to an essay are equivalent to those given by experts, but the time and costs to complete the assessments were largely reduced. Furthermore, the use of gamification helped to increase the amount of students' access to the system in 64.28%; increase in 10.53% the number of essays written and submitted; and improve the quantity and quality of assessments for each essay. Highlights: We proposed a gamified peer assessment (PA) model, where gamification support PA. The final results of the model are equivalent to the correction by experts. Gamification positively influenced on the overall context of Peer Assessment.